2022
DOI: 10.1177/15598276221111046
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoking on the Diagnostic Characteristics of Metabolic Syndrome: A Review

Abstract: Metabolic syndrome is a growing epidemic that increases the risk for cardiovascular disease, diabetes, stroke, and mortality. It is diagnosed by the presence of three or more of the following risk factors: 1) obesity, with an emphasis on central adiposity, 2) high blood pressure, 3) hyperglycemia, 4) dyslipidemia, with regard to reduced high-density lipoprotein concentrations, and 5) dyslipidemia, with regard to elevated triglycerides. Smoking is one lifestyle factor that can increase the risk for metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 170 publications
(263 reference statements)
1
1
0
Order By: Relevance
“…The accumulated local effects plot showed a weak linear relationship, yet still showing higher prevalence of adult smoking linked to higher prevalence of obesity. The association between higher smoking prevalence and obesity is consistent with evidence that heavy cigarette smoking is associated with higher visceral adiposity and a greater risk of obesity compared to light smokers [24,25].…”
Section: Plos Onesupporting
confidence: 82%
“…The accumulated local effects plot showed a weak linear relationship, yet still showing higher prevalence of adult smoking linked to higher prevalence of obesity. The association between higher smoking prevalence and obesity is consistent with evidence that heavy cigarette smoking is associated with higher visceral adiposity and a greater risk of obesity compared to light smokers [24,25].…”
Section: Plos Onesupporting
confidence: 82%
“…In the same way, ex-smokers and current smokers (EXSMOKER, SMOKING) were found to be relevant features; based on this, it has been observed that both smokers and former smokers are predisposed to MetS. This finding is supported by various studies that suggest that smoking can have an adverse impact on blood lipid levels and lead to metabolic disturbances [ 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 54%